2017
DOI: 10.1136/bmjopen-2016-014388
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of UK university students in relation to ultraviolet radiation (UVR) exposure and their sun-related behaviours: a qualitative study

Abstract: ObjectivesTo explore whether knowledge about the harms of ultraviolet radiation (UVR) influences UK university students' sun-related behaviours and examine in depth their attitudes towards: sun protection, natural and artificial tanning behaviours.DesignQualitative methodology with 15 semistructured, individual interviews. Thematic analysis using the Framework Method with analyst triangulation and member validation.SettingOne university in the West Midlands, UK.Participants15 Caucasian male (n=4) and female (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 51 publications
3
49
0
1
Order By: Relevance
“…For instance, those who considered themselves to be at high risk of skin cancer also reported applying sunscreen during daily work. In contrast, qualitative studies in U.K. university students and young Australians showed that key motivators for sun‐related behaviour were the individual's body image influenced by peers, media, family and childhood habits, whereas knowledge about skin cancer and UVR had little influence.…”
Section: Discussionmentioning
confidence: 85%
“…For instance, those who considered themselves to be at high risk of skin cancer also reported applying sunscreen during daily work. In contrast, qualitative studies in U.K. university students and young Australians showed that key motivators for sun‐related behaviour were the individual's body image influenced by peers, media, family and childhood habits, whereas knowledge about skin cancer and UVR had little influence.…”
Section: Discussionmentioning
confidence: 85%
“…e extended period of cold and wintry weather preceding spring 2018 may have encouraged more time outdoors with larger areas of unacclimatised skin exposed to the sun [43,44,69]. Although there was a significant correlation between UV ery daily dose and maximum temperature (Figure 2), the comfortable temperatures meant people may not have taken sun protection precautions [71,72].…”
Section: April-may 2018mentioning
confidence: 99%
“…In general, it is likely that when it is warmer, British people spend more time in the sun [75], particularly with many large outdoor public events occurring in summer months. In warm, fine weather people are likely to have a higher proportion of skin exposed to the sun [43,44]; British people are generally favourable towards a tan and are not always careful when it comes to sun exposure [71,72]. is may have increased vitamin D generation [76] and particularly benefited those with darker skin types (Fitzpatrick skin types IV-VI) [73,74].…”
Section: April-may 2018mentioning
confidence: 99%
“…However, while increasing TYACS knowledge of the risks of sun exposure is a necessity, intentional tanning among GP‐TYAs is driven by a number of physical, attitudinal, and environmental factors . Interventions targeting sun exposure among TYACS should incorporate principles of behavioral science and consider existing interventions conducted in the general population that have shown promise.…”
Section: Discussionmentioning
confidence: 99%